Contrast enhanced magnetic resonance imaging in assessment of aortic atherosclerosis and its relation to severity of myocardial injury due to infarction - A. S. Maksimova (Российский кардиологический журнал, 2019)
Aim. To study the contrast enhanced magnetic resonance imaging (CE-MRI) role in assessment of aortic atherosclerosis and its relation to severity of myocardial injury in myocardial infarction (MI) patients which underwent cardiac MRI before coronary artery bypass grafting and Dor or Menicanti procedures.Material and methods. The study included 42 patients (38 men, 4 women) who underwent CE-MRI (mean age 57,7±8,75 years). In order to analyze the aortic atherosclerosis, axial T1 weighted images before and after 10-15 minutes after CE was evaluated. Along with visual analysis, the diameter, thickness of the aortic wall, and index of enhancement (IE) of T1 weighted image (WI) (TR=400-650 ms, TE=12-20 ms), as the ratio of postand precontrast intensities of the aortic wall: IE=(Intensity T1-WI post-contrast)/ (Intensity T1-WI pre-contrast) were determined. According to the cardiac CEMRI, the proportion of left ventricle (LV) injury as the ratio of the MI injury and theLV mass was estimated.Results. Depending on aortic IE value, patients were divided into three groups: group 1 (9 people) with IE ≤1,05; group 2 (15 people) with 1,05< IE ≤1,15; group 3 (18 people) with IE >1,15. We compared the descending aortic wall thickness and the diameter among these groups. To identify intergroup differences one-way ANOVA with Bonferroni correction was carried out. There were no significant differences in the descending aortic diameters (F=0,15; p=0,86): group 1 — 2,41±0,33, group 2 — 2,54±0,63, group 3 — 2,53±0,51 cm. The thickness of the aortic wall in groups was 2,05±0,58 mm, 3,34±0,68 mm and 3,80±0,46 mm (F=17,39; p< 0,001), respectively. The first and second, first and third groups were distinguished, and there was no significant difference between the second and third groups. Between groups 1, 2 and 3 were also noted the increase and differences in proportion of LV injury, which amounted to 0,11±0,03 with a minimum IE (group 1), with an intermediate IE (group 2) — 0,19±0,08, and with high IE — 0,25±0,15.Conclusion. CE-MRI of the aortic wall can be used as a method of visualizing atherosclerosis and predicting the complications of aortic atherosclerosis. Moreover, the assessment of aortic atherosclerosis can be used in combination with conventional heart examination. The increased CE into the aortic wall in patients with advanced atherosclerosis is usually associated with a greater severity of myocardial injury. During cardiac CE-MRI it is advisable to assess the descending aorta state by calculation of IE T1-WI MRI to clarify the atherosclerosis severity and cardiovascular risk.